2013
DOI: 10.12968/bjom.2013.21.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative working within community maternity services – is this the chink in the armour?

Abstract: Contemporary maternity care in Northern Ireland will be driven by the aims of Midwifery 2020 ( Department of Health (DH), 2010 ), High Quality Woman’ s Health Care ( Royal College of Obstetricians and Gynaecologists (RCOG), 2011 ), Maternity Strategy for Northern Ireland2012–2018 ( Department of Health, Social Services and Public Safety (DHSSPSNI), 2011 ) and Transforming Your Care ( DHSSPSNI, 2011 ). These reports all have at their core the idea of’ promoting normality’ within a maternity service that will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Apart from this, the health care services of both countries monitor the children from birth on up to toddler age; in Australia, this is carried out by child and family health nurses, in Sweden by child health care nurses (Barimani & Hylander, 2008;Homer et al, 2009). In six other studies, the primary interest lies in interprofessional cooperation between midwives and physicians (Ratti et al, 2014;Schölmerich et al, 2014;Shaw, 2013;Skinner & Foureur, 2010;Smith et al, 2009;Vedam et al, 2012). Three studies examine the introduction of child or family health promotion programmes involving various groups of professions (Edvardsson et al, 2011;Edvardsson et al, 2012;Schmied et al, 2015), while four studies focus on the cooperation between professions in the health and social service sectors (Ayerle et al, 2014;Clancy, Gressnes, & Svensson, 2013;Miers & Pollard, 2009;While, Murgatroyd, Ullman, & Forbes, 2006).…”
Section: Cooperation Contextsmentioning
confidence: 99%
See 4 more Smart Citations
“…Apart from this, the health care services of both countries monitor the children from birth on up to toddler age; in Australia, this is carried out by child and family health nurses, in Sweden by child health care nurses (Barimani & Hylander, 2008;Homer et al, 2009). In six other studies, the primary interest lies in interprofessional cooperation between midwives and physicians (Ratti et al, 2014;Schölmerich et al, 2014;Shaw, 2013;Skinner & Foureur, 2010;Smith et al, 2009;Vedam et al, 2012). Three studies examine the introduction of child or family health promotion programmes involving various groups of professions (Edvardsson et al, 2011;Edvardsson et al, 2012;Schmied et al, 2015), while four studies focus on the cooperation between professions in the health and social service sectors (Ayerle et al, 2014;Clancy, Gressnes, & Svensson, 2013;Miers & Pollard, 2009;While, Murgatroyd, Ullman, & Forbes, 2006).…”
Section: Cooperation Contextsmentioning
confidence: 99%
“…A number of studies broach the issue of communication problems between the groups of professions and their effect on collaboration (Barimani & Hylander, 2008;Homer et al, 2009;Nagel-Brotzler et al, 2005;Schölmerich et al, 2014;Schmied et al, 2015;Shaw, 2013;Smith et al, 2009). Poor communication jeopardises the efficacy of working relationships (Murray-Davis et al, 2011;Psaila et al, 2015) and is identified as a 'key barrier' (Shaw, 2013), 'key problem' or as 'an elephant in the room' .…”
Section: Communicationmentioning
confidence: 99%
See 3 more Smart Citations